2002
DOI: 10.1063/1.1497463
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and magnetic properties of Pd100−xFex nanoparticles prepared by ultrasound assisted electrochemistry

Abstract: Nanopowdered alloys of Pd100−xFex, with x=4, 6, 8, and 12, have been prepared by ultrasound assisted electrochemistry. The composition of the individual particles, as determined by x-ray fluorescence, and the bulk composition, as determined by atomic absorption, are in agreement within experimental error. Transmission electron microscopy indicates that the nanopowders consist of agglomerates of small grains with a radius of approximately 5 nm, a radius which is confirmed by the broadening of the reflections in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…Repeating the same Stern-Gerlach deflections of Fe clusters in a molecular beam, Heer et al [8] found instead that the average magnetic moments for small iron clusters (50-230 atoms) drops with the number of atoms when the molecular beam nozzle temperatures are around 300 K. This trend is similar to those observed at room temperature of Co [11], Pd 96 Fe 4 [9,10] [33] and Ni thin films has been observed at room temperature [6,34]. The M S for Fe 3 O 4 thin films [35] drops rapidly when the film decreases from 70 nm.…”
Section: Nanosolid At the Ambient Temperaturesupporting
confidence: 61%
See 2 more Smart Citations
“…Repeating the same Stern-Gerlach deflections of Fe clusters in a molecular beam, Heer et al [8] found instead that the average magnetic moments for small iron clusters (50-230 atoms) drops with the number of atoms when the molecular beam nozzle temperatures are around 300 K. This trend is similar to those observed at room temperature of Co [11], Pd 96 Fe 4 [9,10] [33] and Ni thin films has been observed at room temperature [6,34]. The M S for Fe 3 O 4 thin films [35] drops rapidly when the film decreases from 70 nm.…”
Section: Nanosolid At the Ambient Temperaturesupporting
confidence: 61%
“…Figure 19.1c and d shows the magnetic suppression of Co clusters [11,18] and Ni films. Small Pd 100-x Fe x , grains with x = 4, 6, 8, 12 and a radius of approximately 5 nm at 4.2, 100, and 295 K show typical superparamagnetic features with M S values that are substantially smaller than those observed for the bulk [9]. However, for MnBi films [37], the magnetic momentum changes with neither thickness nor chemical composition.…”
Section: Nanosolid At the Ambient Temperaturementioning
confidence: 78%
See 1 more Smart Citation
“…Fig. 41c and d shows the magnetic suppression of Co clusters [632,637] [630]. However, for MnBi films [653], the magnetic momentum changes with neither thickness nor chemical composition.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that, during cavitation, a jet of liquid penetrates inside the cavitation bubble perpendicular to the 'sonoelectrode' surface [16] and the resulting impact was responsible for dislodging any nanopowder material which had been electrochemically deposited on the surface. This new sonoelectrochemical method has since been employed to produce several pure metallic, alloy [14,[20][21][22] and semiconductor nanoparticles [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%